Restricted vs. unrestricted wheel running in mice: Effects on brain, behavior and endocannabinoids - Biedermann, Sarah Violetta; Ende, Gabriele; Gass, Peter (Hormones and behavior, 2016)
Beneficial effects of voluntary wheel running on hippocampal neurogenesis, morphology and hippocampal-dependent behavior have widely been studied in rodents, but also serious side effects and similarities to stereotypy have been reported. Some mouse strains run excessively when equipped with running wheels, complicating the comparability to human exercise regimes. Here, we investigated how exercise restriction to 6h/day affects hippocampal morphology and metabolism, stereotypic and basal behaviors, as well as the endocannabinoid system in wheel running C57BL/6 mice; the strain most commonly used for behavioral analyses and psychiatric disease models. Restricted and unrestricted wheel running had similar effects on immature hippocampal neuron numbers, thermoregulatory nest building and basal home-cage behaviors. Surprisingly, hippocampal gray matter volume, assessed with magnetic resonance (MR) imaging at 9.4 Tesla, was only increased in unrestricted but not in restricted runners. Moreover, unrestricted runners showed less stereotypic behavior than restricted runners did. However, after blockage of running wheels for 24h stereotypic behavior also increased in unrestricted runners, arguing against a long-term effect of wheel running on stereotypic behavior. Stereotypic behaviors correlated with frontal glutamate and glucose levels assessed by 1H-MR spectroscopy. While acute running increased plasma levels of the endocannabinoid anandamide in former studies in mice and humans, we found an inverse correlation of anandamide with the daily running distance after long-term running. In conclusion, although there are some diverging effects of restricted and unrestricted running on brain and behavior, restricted running does not per se seem to be a better animal model for aerobic exercise in mice.
Gesehen am 18.04.2019
Available online 20 September 2016